Wearable brain-computer interfaces : prototyping EEG-based instruments for monitoring and control /: prototyping EEG-based instruments for monitoring and control. (2023) - Arpaia, P (Pasquale); Esposito, Antonio, 1993-; Gargiulo, Ludovica; Moccaldi, N (Nicola)
No abstract available